Influencer Marketing dalam Brand Strategy Decision pada Campaign HiLo Active Menggunakan Google Looker Studio - Alsa Marsela; Hudi Santoso (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This research examines the role of influencer marketing in making brand strategy decisions for the HiLo Active Protein Berry Fitshake campaign using Google Looker Studio. The focus of the research is analyzing campaign output data, such as engagement rate (ER) and views, to evaluate influencer performance and provide recommendations for future campaigns. The methodology used is a qualitative approach-case study using primary data from TikTok insights and secondary data from the literature. The research results show that influencers A and C have the best performance in ER and views, making it a key consideration for future collaborations. Additionally, influencers F, H, and E have above average ER, while influencers B, G, and J achieve the highest number of views. This study confirms the effectiveness of Google Looker Studio in visualizing data to support brand strategy decision making, especially at the monitoring and evaluation stage.